First, use these rules of exponents to eliminate the eliminate the outer exponent:
a = a^color(red)(1)a=a1 and (x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))(xa)b=xa×b
(4a^-4b^-4)^2 = (4^color(red)(1)a^color(red)(-4)b^color(red)(-4))^color(blue)(2) = 4^(color(red)(1) xx color(blue)(2))a^(color(red)(-4) xx color(blue)(2))b^(color(red)(-4) xx color(blue)(2)) =(4a−4b−4)2=(41a−4b−4)2=41×2a−4×2b−4×2=
4^2a^-8b^-8 = 16a^-8b^-842a−8b−8=16a−8b−8
Now, use this rule of exponents to eliminate the negative exponents:
x^color(red)(a) = 1/x^color(red)(-a)xa=1x−a
16a^color(red)(-8)b^color(red)(-8) = 16/(a^color(red)(- -8)b^color(red)(-
-8)) = 16/(a^color(red)(8)b^color(red)(8))16a−8b−8=16a−−8b−−8=16a8b8